Attributive Adjectives in Standard English and Central Kurdish: A Contrastive Study - Nasradeen Abdul Rahman, Almas; Juma Raheem, Karwan (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
In this paper, the phenomenon of attributive usage of adjectives is analysed in order to clarify the attributive adjectives in English and Kurdish languages. Thus, the researchers, through the present study have investigated the different uses of attributive adjectives and pointed out the similarities and differences between attributive adjectives in English and Kurdish. The present research aims at finding the problematic areas faced by those who deal with this subclass of adjectives in English and Kurdish. The positions of adjectives in both languages are different; some adjectives can be used as attributive and predicative, but while others have to be used either in an attributive or a predicative position. Thus, the present research tackles the syntactic and semantic subclasses of attributive adjectives. The syntactic part has been proposed to account for the function of adjectives. On the semantic features for introducing the quality of the nouns. At last, the attributive adjectives in English and Kurdish have been explained by different examples to point out their different uses, both syntactically and semantically.